Intracranial hypertension associated with treatment of acute promyelocytic leukemia with all-trans retinoic acid (ATRA): a case report - Alvarenga , Tarcísio N; Sousa-Santos, Patrick Emanuell; Pozzobon, Pedro Machry; Santos, Itamar Meireles; Baston, Ana Beatriz; Teixeira, Igor de Lima e (Headache Medicine, 2022)
Case presentation Female, 18 years-old, without relevant family history, referred to Neurology by Hematology for headache. 3 years ago, she was diagnosed with Acute Promyelocytic Leukemia (APL) currently on maintenance therapy with All-Trans Retinoic Acid (ATRA). The patient reports that in all previous cycles presented headache with the following characters: one-side temporal location, pulsating quality, moderate intensity, with nausea and vomiting, photophobia and phonophobia, uncertain duration, with simple analgesics response. In the current cycle, she relates continuous pain, severe intensity and unresponsive to medication. On examination, there were no focal neurological findings and on funduscopic examination there was no papilledema. MRI and laboratorial tests were normal. Cerebrospinal fluid (CSF) opening pressure was 35 cmH2O, no other alterations. 15 milliliters of CSF were removed, with a closing pressure of 25 cmH2O. A hypothesis of Intracranial Hypertension associated with use of ATRA was made. Afterwards, there was important improvement of the headache, with residual pain of mild intensity. Therefore, Acetazolamide was started at a dose of 250 milligrams every 12 hours with complete resolution of symptoms. Discussion Acute myeloid leukemia (AML) comprises a heterogeneous group of aggressive blood cell cancers that arise from clonal expansion of malignant hematopoietic precursor cells in the bone marrow. Acute promyelocytic leukemia (APL) is a biologically and clinically distinct variant of AML. APL is classified as acute promyelocytic leukemia with PML-RARA. The cytogenetic hallmark of APL is a translocation involving RARA, the retinoic acid receptor alpha locus on chromosome 17. Without treatment, APL is the most malignant form of AML, with a median survival of less than one month. (To see the complete abstract, please, check out the PDF).